How do electronic risk assessment tools affect the communication and understanding of diagnostic uncertainty in the primary care consultation? A systematic review and thematic synthesis. Issue 6 (29th June 2022) - Burns, Alex; Donnelly, Brian; Feyi-Waboso, Joshua; Shephard, Elizabeth; Calitri, Raff; Tarrant, Mark; Dean, Sarah Gerard
Abstract : Objectives: To conduct a systematic review and synthesise qualitative research of electronic risk assessment tools (eRATs) in primary care, examining how they affect the communication and understanding of diagnostic risk and uncertainty. eRATs are computer-based algorithms designed to help clinicians avoid missing important diagnoses, pick up possible symptoms early and facilitate shared decision-making. Design: Systematic search, using predefined criteria of the published literature and synthesis of the qualitative data, using Thematic Synthesis. Database searches on 27 November 2019 were of MEDLINE, Embase, CINAHL and Web of Science, and a secondary search of the references of included articles. Included studies were those involving electronic risk assessment or decision support, pertaining to diagnosis in primary care, where qualitative data were presented. Non-empirical studies and non-English language studies were excluded. 5971 unique studies were identified of which 441 underwent full-text review. 26 studies were included for data extraction. A further two were found from citation searches. Quality appraisal was via the CASP (Critical Appraisal Skills Program) tool. Data extraction was via line by line coding. A thematic synthesis was performed. Setting: Primary care. Results: eRATs included differential diagnosis suggestion tools, tools which produce a future risk of disease development or recurrence or calculate a risk of current undiagnosed disease. Analytical themes were developed to describe separate aspects of the clinical consultation where risk and uncertainty are both central and altered via the use of an eRAT: 'Novel risk', 'Risk refinement', 'Autonomy', 'Communication', 'Fear' and 'Mistrust'. Conclusion: eRATs may improve the understanding and communication of risk in the primary care consultation. The themes of 'Fear' and 'Mistrust' could represent potential challenges with eRATs. Trial registration number: CRD219446.